Male Role Norms, Heavy Drinking, and Bystander Behavior for Sexual Aggression - Leone, Ruschelle M. (J Interpers Violence, 2019)
Bystander training programs have proliferated on college campuses to prevent alcohol and non–alcohol-related sexual aggression. However, many programs fail to address the effects of a bystander’s alcohol use on intervention. This is not surprising due to the limited research examining this association. To this end, the present study examined how heavy drinking and a known correlate of intervention, men’s adherence to traditional masculinity, are jointly and independently associated with bystander behavior in drinking contexts. Participants were 148 community men between the ages of 21 and 30 who completed measures of heavy drinking, adherence to traditional male role norms, and prior bystander behavior in drinking contexts aimed at helping friends and strangers. Hierarchical linear regressions demonstrated that adherence to the belief that men should attain social status was associated with more frequent bystander behavior for friends, whereas adherence to the belief that men should avoid stereotypical feminine activities was associated with less frequent bystander behavior for friends. In addition, the relation between adherence to the belief that men should avoid stereotypical feminine activities and bystander behavior for friends was significant and negative among heavy drinkers but not among non-heavy drinkers. Findings suggest that men who avoid stereotypical feminine activities may be most inhibited from intervening to help friends in party contexts if they are heavy, compared with non-heavy, drinkers. These men are likely consuming alcohol in these party contexts and may benefit from targeted, gender-specific, interventions.